SISTEM INFORMASI PENJUALAN KARTU UNDANGAN BERBASIS WEB - Dedi Rahman Habibie; Sapta Eka Putra (Lembaga Pengembangan Kinerja Dosen, 2022)
Currently, the development of information technology is not only limited to providing information, but has also penetrated the world of digital commerce on a website basis. The sales information system that is built on a website basis can display information quickly and accurately. In the system that is running at the AR Invitation Printing Shop, there are many problems that occur such as ordering designs and printing invitations that are still done manually. In placing an order, consumers must come to the location of the AR Invitation Printing Shop, in other words, consumers must meet face to face. Based on these problems, the authors want to build a Website Ordering Information System Online with the help of the programming language Php, My SQL, and Code Igniter. With this website, consumers can communicate with sellers, looking for the product they want without having to come to the printing shop.